A study of sertraline in dialysis (ASSertID): a protocol for a pilot randomised controlled trial of drug treatment for depression in patients undergoing haemodialysis. Issue 1 (December 2015) - Friedli, Karin; Almond, Michael; Day, Clara; Chilcot, Joseph; Gane, Maria; Davenport, Andrew; Guirguis, Ayman; Fineberg, Naomi; Spencer, Benjamin; Wellsted, David; Farrington, Ken
Abstract Background The prevalence of depression in people receiving haemodialysis is high with estimates varying between 20 and 40 %. There is little research on the effectiveness of antidepressants in dialysis patients with the few clinical trials suffering significant methodological issues. We plan to carry out a study to evaluate the feasibility of conducting a randomised controlled trial in patients on haemodialysis who have diagnosed Major Depressive Disorder. Methods/Design The study has two phases, a screening phase and the randomised controlled trial. Patients will be screened initially with the Beck Depression Inventory to estimate the number of patients who score 16 or above. These patients will be invited to an interview with a psychiatrist who will invite those with a diagnosis of Major Depressive Disorder to take part in the trial. Consenting patients will be randomised to either Sertraline or placebo. Patients will be followed-up for 6 months. Demographic and clinical data will be collected at screening interview, baseline interview and 2 weeks, and every month (up to 6 months) after baseline. The primary outcome is to evaluate the feasibility of conducting a randomised, double blind, placebo pilot trial in haemodialysis patients with depression. Secondary outcomes include estimation of the variability in the outcome measures for the treatment and placebo arms, which will allow for a future adequately powered definitive trial. Analysis will primarily be descriptive, including the number of patients eligible for the trial, drug exposure of Sertraline in haemodialysis patients and the patient experience of participating in this trial. Discussion There is an urgent need for this research in the dialysis population because of the dearth of good quality and adequately powered studies. Research with renal patients is particularly difficult as they often have complex medical needs. This research will therefore not only assess the outcome of anti-depressants in haemodialysis patients with depression but also the process of running a randomised controlled trial in this population. Hence, the outputs of this feasibility study will be used to inform the design and methodology of a definitive study, adequately powered to determine the efficacy of anti-depressants in patient on haemodialysis with depression. Trial registration ISRCTN registryISRCTN06146268 and EudraCT reference: 2012-000547-27.